Patient Perceptions and Preferences Regarding Telemedicine for Autoimmune Rheumatic Diseases Care During the COVID‐19 Pandemic. Issue 7 (13th April 2022) - Danila, Maria I.; Gavigan, Kelly; Rivera, Esteban; Nowell, W. Benjamin; George, Michael D.; Curtis, Jeffrey R.; Christopher‐Stein, Lisa; Banerjee, Shubhasree; Merkel, Peter A.; Young, Kalen; Shaw, Dianne G.; Gordon, Jennifer; et al.
Abstract : Objective: To assess the perceptions and preferences of telemedicine among patients with autoimmune rheumatic diseases during the COVID‐19 pandemic. Methods: We conducted an online survey among patients with autoimmune rheumatic diseases. Attitudes about telemedicine (i.e., telemedicine acceptability), evaluated using the validated Telemedicine Perception Questionnaire (TMPQ), and visit satisfaction were assessed for different telemedicine experiences and types of autoimmune rheumatic disease. Results: Of 3, 369 invitations, 819 responses were received. Participants had a mean ± SD age of 58.6 ± 11.6 years and were mostly White (n = 759, or 92.7%) and female (n = 702, or 85.7%). Of the 618 participants who said that telemedicine was available to them, 449 (72.7%) reported having a telemedicine visit, with 303 (67.5%) reporting attending a telemedicine video visit. On a 0 to 10 scale, the mean ± SD visit satisfaction score was 7.3 ± 1.8, with 25.8% of respondents being very satisfied (scores of 9 or 10). Video visits and higher TMPQ scores were associated with higher satisfaction. Compared to those who did not experience a telemedicine visit, patients who did were more likely to prefer telemedicine (video or phone) for routine visits (73.7% versus 44.3%; P < 0.001), reviewing test results (64.8% versus 53.8%; P < 0.001), when considering changing medications (40.5% versus 26.8%; P < 0.001), and when starting a new injectable medication (18.9% versus 12.7%; P = 0.02). Conclusion: During the COVID‐19 pandemic, patients with autoimmune rheumatic diseases frequently had telemedicine visits, with the majority held via video, and were satisfied with these visits. These results suggest that because patients prefer telemedicine for certain visit reasons, maximizing effective use of telemedicine will require personalized patient scheduling.